Clinical experience in the management of pulmonary opportunist infection and rejection in recipients of heart-lung transplants. Issue 10 (October 1988) - Penketh, A R; Higenbottam, T W; Hutter, J; Coutts, C; Stewart, S; Wallwork, J
Abstract : The main clinical problems that follow heart-lung transplantation are opportunist infections of the lungs and pulmonary rejection. Of 23 patients undergoing heart-lung transplantation, eight had opportunist infections and 12 had at least one episode of pulmonary rejection. Cardiac rejection occurred in only one patient, who did not need treatment. Of the 12 patients who had pulmonary rejection, nine recovered fully after augmented immunosuppression with high dose corticosteroids, although one patient required additional low dose corticosteroids for eight months before making a full recovery. Fatal opportunist lung infection followed treatment for rejection in two patients. One patient developed obliterative bronchiolitis. Of the eight patients with opportunist infections, five had primary cytomegalovirus pneumonitis, acquired from the donor. All three patients treated with acyclovir died, whereas the two treated with hyperimmune globulin and dihydroxy proxymethylguanine recovered fully. Two patients developed Pneumocystis carinii pneumonia, which was treated successfully in one patient with intravenous sulphadimidine and trimethoprim. The other patient died after a further episode of rejection and aspergillus bronchitis. One patient developed a tuberculous empyema. The calculated actuarial survival at one year was 78% and at two years 67.2%. Although it is still in its innovative stage heart-lung transplantation appears to have complications and results similar to those of transplantation of other organs.